Flame-retardant composites, methods of making and using the same

CN117976908BActive Publication Date: 2026-10-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410166487.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2026-10-27
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

然而,当前研发的微胶囊尺寸相对较大,对电池电化学性能仍存在一定的影响,因此亟需研发更小尺寸的新型微胶囊

Benefits of technology

[0025]本申请的阻燃复合材料的结构由众多具有胶囊结构的阻燃复合材料,相互交联构成的3D互联网状结构。其中,胶囊结构即导电有机层包覆阻燃剂的结构,是由多个胶囊结构形成具有间隙结构的团聚型阻燃复合材料,并且多个团聚型阻燃复合材料相互交联,最终构成的3D互联网状结构。这种3D互联网状结构通常具有较多的分子间隙,为锂离子提供了许多的嵌入位点。另外,3D互联网状结构也为锂离子和电子的传输提供了一个快速的网络通道。因此,该阻燃复合材料添加到电池中,有利于降低电池内阻和提高电池倍率性能;并且在电池即将或正在发生热失控时,导电有机层能够及时破裂释放阻燃剂,从而抑制电池热失控的发生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117976908B_ABST
    Figure CN117976908B_ABST
Patent Text Reader

Abstract

The application provides a kind of flame-retardant composite material and its preparation method and application, and the flame-retardant composite material includes at least two crosslinked flame-retardant particles, the flame-retardant particle includes flame retardant, and the conductive organic layer is coated on the surface of the flame retardant, there is a gap between adjacent two flame-retardant particles, and the average particle size of the flame-retardant particle is 10nm-50nm.The application is formed by the agglomeration of flame-retardant particles, and a gap is formed between adjacent flame-retardant particles, which increases the specific surface area of the flame-retardant composite material, improves the conductivity of the conductive organic layer, and when the thermal runaway temperature is reached, the conductive organic layer can be broken to release the flame retardant, thereby improving the safety performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a flame-retardant composite material, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries have become the mainstream power battery type due to their advantages such as high energy density, long cycle life, and low self-discharge rate. However, with the continuous pursuit of higher energy density and ultra-fast charging technology, lithium-ion batteries still face a series of challenges in terms of energy density, cycle life, charging rate, and safety, especially safety issues such as fire and explosion.

[0003] In traditional technologies, the safety of automotive power batteries primarily relies on the integration of battery management systems (BMS), thermal management systems, fire control and extinguishing systems, safety valves, and circuit breakers. It also involves the development of highly safe separators, electrode materials, and electrolytes. In the safety protection of lithium-ion batteries, the use of flame retardants is an effective technical means; however, this often comes at the cost of sacrificing battery electrochemical performance. Currently, synthesizing flame-retardant microcapsules is considered an effective way to reduce the impact of flame retardants on battery electrochemical performance. However, the currently developed microcapsules are relatively large, still having some impact on battery electrochemical performance. Therefore, there is an urgent need to develop novel microcapsules with smaller sizes. Summary of the Invention

[0004] Therefore, this application provides a flame-retardant composite material formed by the agglomeration of flame-retardant particles and the creation of gaps between adjacent particles, thereby increasing the specific surface area of ​​the composite material and improving the conductivity of the conductive organic layer. Furthermore, when the battery is about to or is experiencing thermal runaway, the conductive organic layer can rupture and release the flame retardant, thus improving the battery's safety performance. Further, this application also provides a method for preparing the aforementioned flame-retardant composite material and its application.

[0005] In a first aspect, this application provides a flame-retardant composite material comprising at least two cross-linked flame-retardant particles, wherein each flame-retardant particle comprises a flame retardant agent and a conductive organic layer coated on the surface of the flame retardant agent, wherein there is a gap between two adjacent flame-retardant particles, and the average particle size of the flame-retardant particles is 10 nm to 50 nm.

[0006] In some embodiments, the average particle size of the flame-retardant composite material is 30 nm to 200 nm.

[0007] In some embodiments, the flame retardant includes at least one of phosphorus-based flame retardants, nitrogen-based flame retardants, halogen-based flame retardants, metal compound flame retardants, and electrolyte curing agents.

[0008] In some embodiments, the material of the conductive organic layer includes at least one of ion-conducting organic materials and electronically conductive organic materials.

[0009] Optionally, the material of the conductive organic layer includes at least one of polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polymeric polyether (PPE), polyaniline (PANI), polythiophene (PEDOT), and polyacetylene (PAA).

[0010] In some embodiments, the average thickness of the conductive organic layer is 20 nm to 50 nm.

[0011] Secondly, this application provides a method for preparing a flame-retardant composite material, the method comprising:

[0012] Prepare a first mixture containing a flame retardant and a conductive polymeric monomer;

[0013] An initiator is added to the first mixture to cause the conductive polymer monomer to undergo a polymerization reaction on the surface of the flame retardant, thereby obtaining a second mixture;

[0014] At the polymerization temperature, a dissolved salt is added to the second mixture at a saturated concentration. The second mixture is then centrifuged and dried to prepare the flame-retardant composite material. The flame-retardant composite material comprises at least two cross-linked flame-retardant particles. Each flame-retardant particle comprises a flame retardant and a conductive organic layer coated on the surface of the flame retardant. There is a gap between two adjacent flame-retardant particles.

[0015] In some embodiments, the polymerization reaction is carried out at a temperature of 75°C to 85°C.

[0016] In some embodiments, the dissolved salt includes at least one of sodium chloride, potassium chloride, and magnesium chloride.

[0017] In some embodiments, the first mixture further includes an emulsifier; optionally, the emulsifier includes at least one of sodium dodecylbenzenesulfonate, nonylphenol ethylene oxide ether, triethanolamine, azobisisobutyronitrile, and sodium dodecyl sulfate.

[0018] In some embodiments, the initiator includes at least one of ammonium persulfate, ester peroxide, and benzoyl peroxide.

[0019] In some embodiments, the flame retardant includes one or more of phosphorus-based flame retardants, nitrogen-based flame retardants, halogen-based flame retardants, metal compound flame retardants, and electrolyte curing agents.

[0020] In some embodiments, the mass ratio of the flame retardant to the conductive polymeric monomer is (1~3):1.

[0021] In some embodiments, the mass ratio of the initiator to the conductive polymer monomer is 1:(80~120).

[0022] In some embodiments, the centrifugation speed is 8000 rpm to 9800 rpm.

[0023] Thirdly, this application provides a battery comprising a flame-retardant composite material as described in the first aspect or a flame-retardant composite material prepared using the method for preparing a flame-retardant composite material as described in the second aspect.

[0024] Compared with traditional technologies, this application has at least the following beneficial effects:

[0025] The flame-retardant composite material of this application comprises a 3D internet-like structure formed by the cross-linking of numerous flame-retardant composite materials with capsule structures. The capsule structure, i.e., the structure of a conductive organic layer encapsulating the flame retardant, is an aggregated flame-retardant composite material with interstitial structures formed by multiple capsule structures, and these aggregated flame-retardant composite materials are cross-linked to ultimately form a 3D internet-like structure. This 3D internet-like structure typically has numerous intermolecular gaps, providing many insertion sites for lithium ions. Furthermore, the 3D internet-like structure also provides a rapid network channel for the transport of lithium ions and electrons. Therefore, adding this flame-retardant composite material to a battery helps reduce internal resistance and improve rate performance; and when the battery is about to or is experiencing thermal runaway, the conductive organic layer can rupture in time to release the flame retardant, thereby suppressing the occurrence of battery thermal runaway. Attached Figure Description

[0026] Figure 1 This is an electron microscope image of the flame-retardant composite material provided in Example 1 of this application.

[0027] Figure 2 This is another electron microscope image of the flame-retardant composite material provided in Example 1 of this application.

[0028] Figure 3 This is an electron microscope image of the flame-retardant composite material provided in Comparative Example 1 of this application. Detailed Implementation

[0029] The present application will be further described in detail below with reference to the accompanying drawings, embodiments, and examples. These embodiments and examples are for illustrative purposes only and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to enable a more thorough and comprehensive understanding of the disclosure of the present application. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. Furthermore, numerous specific details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0030] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.

[0031] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0032] In this application, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," etc., serve only a non-exhaustive enumeration purpose and should be understood as not constituting a closed limitation on quantity.

[0033] All references to this invention are incorporated herein by reference as if each document were individually incorporated by reference. Unless they conflict with the inventive purpose and / or technical solution of this application, the referenced documents involved in this invention are incorporated in their entirety and for all purposes. When references are made in this invention, the definitions of relevant technical features, terms, nouns, phrases, etc., are also incorporated herein by reference. When references are made in this invention, examples and preferred embodiments of the relevant technical features cited may also be incorporated herein by reference, but only to the extent that they enable the implementation of this invention. It should be understood that when the cited content conflicts with the description in this application, this application shall prevail or modifications shall be made adaptively based on the description in this application.

[0034] In traditional technologies, directly adding flame retardants to batteries may affect their electrochemical performance. This application, however, utilizes cross-linking on the outer surface of a conductive organic layer to create a gap structure in the flame-retardant composite material, increasing ion transport channels and ensuring the battery's electrochemical performance. Furthermore, when the battery is about to or is experiencing thermal runaway, the cross-linking sites preferentially break, causing the individual flame-retardant particles to separate, improving their dispersibility. As the flame-retardant particles further disperse into the battery, the rupture of the conductive organic layer on the particle surface releases the flame retardant, effectively enhancing battery safety.

[0035] The first aspect of this application provides a flame-retardant composite material, the flame-retardant composite material comprising at least two cross-linked flame-retardant particles, each flame-retardant particle comprising a flame retardant agent and a conductive organic layer coated on the surface of the flame retardant agent, with a gap between adjacent flame-retardant particles, the average particle size of the flame-retardant particles being 10nm~50nm, for example, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm.

[0036] The flame-retardant composite material of this application uses a conductive organic layer as the shell of the flame retardant. Through cross-linking on the outer surface of the conductive organic layer, the flame-retardant composite material has an interstitial structure, increasing ion transport channels and ensuring the electrochemical performance of the battery. Furthermore, when the battery is about to or is experiencing thermal runaway, the cross-linking sites preferentially break, causing the individual flame-retardant particles to break apart, improving the dispersibility of the flame-retardant particles. When the flame-retardant particles are fully dispersed in the battery, the release of the flame retardant as the conductive organic layer on the surface of the flame-retardant particles breaks down effectively improves battery safety.

[0037] Furthermore, this application controls the average particle size of the flame-retardant particles, thereby effectively ensuring that a stable cross-linked structure can be formed between the flame-retardant particles and that there are stable gaps between the flame-retardant particles, thus improving the conductivity of the flame-retardant composite material. If the average particle size of the flame-retardant particles is relatively large, it may result in an excessively large gap structure, which is not conducive to the ion transport performance of the gap structure and causes severe adhesion between the particles. If the average particle size of the flame-retardant particles is relatively small, it will result in a smaller amount of flame retardant coating, affecting the flame-retardant effect.

[0038] It is understood that the conductive organic layer refers to a coating layer formed of conductive organic materials. This conductive organic layer not only enables ion transport but also allows for timely rupture and release of flame retardants during battery thermal runaway, thus improving battery safety. In this application, both flame-retardant capsules and flame-retardant particles refer to structures in which flame retardants are coated by a conductive organic layer.

[0039] It is understood that the flame retardant in this application can be a material that prevents the battery from undergoing a combustion reaction, or a material that can block the combustion of the battery after it has started to burn, thereby achieving the purpose of extinguishing the fire. The flame retardant mechanism can be endothermic, covering, chain reaction inhibition, and asphyxiation by non-flammable gases. The endothermic effect of the flame retardant refers to its ability to absorb heat generated during the thermal runaway and combustion reaction stages in a short time, thereby preventing and controlling the further occurrence of the heat generation and combustion reactions. The covering effect of the flame retardant refers to its ability to form a barrier layer at thermal runaway temperatures, isolating the battery active materials from oxygen, providing heat insulation, oxygen isolation, and preventing the escape of flammable gases, thus achieving the flame retardant purpose. The chain reaction inhibition effect of the flame retardant refers to its ability to capture free radicals during the reaction process during the thermal runaway and combustion stages, thereby interfering with the heat generation and combustion reactions. For example, the flame retardant can react with the active materials or solidify the electrolyte, thereby preventing the heat generation reaction from proceeding. The asphyxiation effect of flame retardants on non-flammable gases refers to the fact that when flame retardants are heated, they decompose into non-flammable gases, diluting the concentration of flammable gases released from combustible materials to below the lower flammability limit. At the same time, they also dilute the oxygen concentration in the combustion zone, preventing the continuation of combustion and thus achieving the effect of flame retardancy.

[0040] Understandably, in the production and application of flame retardants, a single flame retardant often cannot achieve the desired effect. However, multiple flame retardants can be compounded to produce a synergistic inhibition effect. Combining two or more flame retardants and optimizing them from the perspectives of performance, economics, and social benefits yields the optimal compounded flame retardant. Compounding flame retardants allows for complementary performance between different flame retardants, improving inhibition performance and reducing dosage, thus greatly expanding the application range and effectiveness of flame retardants.

[0041] In some embodiments, the flame-retardant composite material comprises 3 to 5 cross-linked flame-retardant particles.

[0042] In some embodiments, the average particle size of the flame-retardant composite material is 30nm to 200nm, for example, it can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm or 200nm.

[0043] This application controls the average particle size of the flame-retardant composite material to avoid the formation of a 3D internet-like structure with poor dispersibility, thereby improving the material's dispersibility and thus affecting the battery's conductivity. Moreover, during battery thermal runaway, the cross-linked flame-retardant composite material is not easy to disperse, thereby reducing the flame-retardant effect of the flame retardant.

[0044] In some embodiments, the flame retardant may be an inorganic flame retardant or an organic flame retardant.

[0045] In some embodiments, the flame retardant includes at least one of phosphorus-based flame retardants, nitrogen-based flame retardants, halogen-based flame retardants, metal compound flame retardants, and electrolyte curing agents.

[0046] In some embodiments, the material of the conductive organic layer includes at least one of ion-conducting organic materials and electronically conductive organic materials.

[0047] Optionally, the material of the conductive organic layer includes at least one of polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polymeric polyether (PPE), polyaniline (PANI), polythiophene (PEDOT), and polyacetylene (PAA).

[0048] In some embodiments, the average thickness of the conductive organic layer is 20nm to 50nm, for example, it can be 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 48nm or 50nm.

[0049] A second aspect of this application provides a method for preparing a flame-retardant composite material, the method comprising:

[0050] Prepare a first mixture containing a flame retardant and a conductive polymeric monomer;

[0051] An initiator is added to the first mixture to cause the conductive polymer monomer to undergo a polymerization reaction on the surface of the flame retardant, thereby obtaining a second mixture;

[0052] At the temperature of the polymerization reaction, a dissolved salt is added to the second mixture, the concentration of the dissolved salt in the second mixture being saturated. The second mixture is then dried to prepare the flame-retardant composite material. The flame-retardant composite material comprises at least two cross-linked flame-retardant particles. Each flame-retardant particle comprises a flame retardant and a conductive organic layer coated on the surface of the flame retardant. There is a gap between two adjacent flame-retardant particles.

[0053] After the polymerization reaction is complete, a saturated concentration of dissolved salt is added, and the mixture is directly centrifuged at the polymerization temperature. During centrifugation, the solution temperature gradually decreases, causing the flame-retardant composite material to precipitate. The resulting flame-retardant particles are small in size and have a cross-linked structure, forming a flame-retardant composite material composed of multiple cross-linked flame-retardant particles with interstitial structures. These multiple cross-linked flame-retardant composite materials constitute a 3D internet-like structure. The interstitial and internet-like structures function as ion transport channels, effectively ensuring the conductivity and safety of the flame-retardant particles in the battery.

[0054] It should be noted that in this application, the two flame-retardant particles are cross-linked, that is, during the process of forming the conductive organic layer, some flame-retardant particles agglomerate, causing the conductive organic layers of the flame-retardant particles to polymerize and cross-link and agglomerate, thereby forming a flame-retardant composite material with a gap structure. The cross-linking of multiple flame-retardant composite materials constitutes a 3D Internet-like structure.

[0055] In some embodiments, the temperature of the polymerization reaction is 75°C to 85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C.

[0056] This application controls the temperature of the polymerization reaction to ensure the polymerization rate, enabling the monomers to coat the surface of the flame retardant material. If the polymerization temperature is relatively high, the monomers may not be able to completely coat the flame retardant material; if the polymerization temperature is relatively low, the polymerization rate may be slow, which not only affects production efficiency but also results in large flame retardant composite material particles with few interstitial structures, thus affecting the electrochemical performance of the battery.

[0057] In some embodiments, the dissolved salt includes at least one of sodium chloride, potassium chloride, and magnesium chloride.

[0058] In some embodiments, the first mixture further includes an emulsifier; optionally, the emulsifier includes at least one of sodium dodecylbenzenesulfonate, nonylphenol ethylene oxide ether, triethanolamine, azobisisobutyronitrile, and sodium dodecyl sulfate.

[0059] In some embodiments, the initiator includes at least one of ammonium persulfate, ester peroxide, and benzoyl peroxide.

[0060] In some embodiments, the conductive polymeric monomer includes at least one of methyl methacrylate (PMMA), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polymeric polyether (PPE), polyaniline (PANI), polythiophene (PEDOT), and polyacetylene (PAA).

[0061] In some embodiments, the flame retardant includes at least one of phosphorus-based flame retardants, nitrogen-based flame retardants, halogen-based flame retardants, metal compound flame retardants, and electrolyte curing agents.

[0062] In some embodiments, halogenated flame retardants include one or more of chlorinated and brominated flame retardants. Chlorinated flame retardants include categories such as chlorinated polyolefins, chlorinated polyalkane, chlorinated diphenyl ethers, and chlorinated benzene, specifically including but not limited to the following flame retardants: chlorinated polyethylene (CPE), chlorinated polypropylene (CPP), chlorinated paraffin, decachlorodiphenyl ether, hexachlorobenzene, and novel high-performance chlorinated flame retardants, such as tetrachlorophthalic anhydride, tetrachlorobisphenol A, hexachlorocyclopentadiene, bis(hexachlorocyclopentadiene)cyclooctane, perchlorocyclopentanedecane, tetrachlorophthalic anhydride, and chlorobacterial acid. Brominated flame retardants can be classified according to their structure into polybrominated diphenyl ethers, bromophenols, bromobisphenol A, bromophthalic acids, bromopolyols, and bromoalkanes. This includes, but is not limited to, the following flame retardants: polybrominated diphenyl ethers (PBDEs), 2,4,6-tribromophenol, tetrabromobisphenol A (TBBPA), tetrabromobisphenol A-bis(2,3-dialkylpropyl) ether (TBAB), hexabromocyclododecane (HBCD), brominated polystyrene (BPS), brominated epoxy, decabromodiphenyl ethane, decabromodiphenyl ether, tetrabromobisphenol A, brominated polystyrene, tribromophenol and its derivatives, bromotriazine, brominated epoxy resin, hexabromocyclododecane, tetrabromobisphenol A polycarbonate oligomers, dibromoneopentyl glycol, tetrabromophthalic anhydride, tetrabromophthalic anhydride diol, melamine bromate, potassium perfluorobutyl sulfonate, and Declone flame retardants.

[0063] In some embodiments, phosphorus-based flame retardants include red phosphorus flame retardants, ammonium salt flame retardants, phosphate ester compounds, phosphaphenanthrene compounds, polyphosphazene compounds, hypophosphite and its salt compounds, and triazine or piperazine charring agents. Specific flame retardants include, but are not limited to: red phosphorus, ammonium polyphosphate, melamine phosphate and melamine polyphosphate, melamine cyanurate, bisphenol A bis(diphenyl) phosphate, resorcinol (diphenyl) phosphate, tris(2-chloroethyl) phosphate, tris(1-chloro-2-propyl) phosphate, 10-(2,5-dihydroxyphenyl)-10-hydro-9-oxa-10-phosphaphenanthrene-10-oxide (ODOPB), diethylaluminum hypophosphite, 2-carboxyethylphenyl hypophosphite, and aluminum hypophosphite.

[0064] In some embodiments, nitrogen-based flame retardants include one or more of nitrogen-containing polyamides, nitrogen-containing polyurethanes, phosphonamides, melamine, and ammonium polyphosphate.

[0065] In some embodiments, the metal compound flame retardant includes magnesium-based flame retardants (magnesium hydroxide), antimony-based flame retardants (antimony oxide, sodium antimonate), aluminum hydroxide, zinc borate, molybdenum oxide, and ammonium molybdate.

[0066] In some embodiments, the electrolyte curing agent refers to an agent capable of interacting with the electrolyte to control its dielectric constant or viscosity, aiming to suppress Joule heating by forcibly increasing internal resistance by disrupting ionic conductivity. The curing agent can increase the viscosity of the electrolyte, transforming the liquid electrolyte into a non-conductive solid or gel-like substance. Optionally, the electrolyte curing agent includes one or more of glycol and amine compounds. For example, amine curing agents include, but are not limited to: 1,3-propanediamine, benzylamine, dibenzylamine (DBA), 1,2-ethylenediamine (1,2-EDA), and trihexylamine (THA); glycol curing agents include, but are not limited to: 1,2-ethylenediol, 1,3-propanediol, and 1,5-pentanediol.

[0067] In some embodiments, the mass ratio of the flame retardant to the conductive polymer monomer is (1~3):1, for example, it can be 1.0:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2.0:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3.0:1.

[0068] In some embodiments, the mass ratio of the initiator to the conductive polymer monomer is 1:(80~120), for example, it can be 1:80, 1:84, 1:88, 1:92, 1:96, 1:100, 1:104, 1:108, 1:112, 1:116 or 1:120.

[0069] In some embodiments, the centrifugation speed is 8000 rpm to 9800 rpm, for example, it can be 8000 rpm, 8100 rpm, 8200 rpm, 8300 rpm, 8400 rpm, 8500 rpm, 8600 rpm, 8700 rpm, 8800 rpm, 8900 rpm, 9000 rpm, 9100 rpm, 9200 rpm, 9300 rpm, 9400 rpm, 9500 rpm, 9600 rpm, 9700 rpm, or 9800 rpm.

[0070] This application controls the centrifugal speed to control the precipitation rate of the flame-retardant composite material, thereby obtaining a flame-retardant composite material with uniform size.

[0071] A third aspect of this application provides a battery comprising a flame-retardant composite material as described in the first aspect or a flame-retardant composite material prepared using the method for preparing a flame-retardant composite material as described in the second aspect.

[0072] In some embodiments, the battery includes a housing filled with electrolyte, and a cell immersed in electrolyte is disposed within the housing. The cell includes a positive electrode and a negative electrode stacked together, and a separator is disposed between the positive electrode and the negative electrode.

[0073] In some embodiments, the positive electrode includes a positive current collector and a positive active layer disposed on the surface of the positive current collector. The positive active layer includes a positive active material, a binder, and a conductive agent. The conductive agent includes the flame-retardant composite material.

[0074] Optionally, in the positive electrode active layer, the flame-retardant composite material accounts for 10% to 100% of the total mass of the conductive agent, preferably 40% to 60%.

[0075] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active layer disposed on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, a binder, and a conductive agent. The conductive agent includes the flame-retardant composite material.

[0076] Optionally, in the negative electrode active layer, the flame-retardant composite material accounts for 10% to 100% of the total mass of the conductive agent, preferably 40% to 60%.

[0077] In some embodiments, the electrolyte includes the flame-retardant composite material. The flame-retardant composite material accounts for 1% to 15% of the mass of the electrolyte.

[0078] The embodiments of the present invention will be described in detail below with reference to examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this invention, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0079] The average particle size was obtained through image shadow statistics using transmission electron microscopy. The average thickness was calculated by averaging the maximum and minimum thicknesses of the shell obtained using transmission electron microscopy.

[0080] Example 1

[0081] Weigh 0.2g of ammonium polyphosphate and dissolve it in 3mL of methyl methacrylate monomer. Sonicate for 10min to disperse evenly and obtain the first solution.

[0082] Weigh 0.4g of sodium dodecylbenzenesulfonate and dissolve it in 80mL of deionized water. Stir mechanically for 10min to disperse it evenly and obtain a second solution.

[0083] The first solution was added dropwise to the second solution and stirred to disperse it evenly. Then, it was emulsified for 30 minutes to obtain the first mixture.

[0084] Argon gas was introduced into the first emulsified mixture and stirred for 30 minutes. Then, the mixture was heated to 75°C and 0.3 g of ammonium sulfate was added. The mixture was reacted for 5 hours to obtain the second mixture.

[0085] After the reaction is complete, heating of the second mixed solution is stopped, and sodium chloride is added to the second mixed solution at 75°C to achieve a saturated concentration of sodium chloride. The solution is then centrifuged at 9600 rpm and dried to obtain the flame-retardant composite material.

[0086] like Figure 1 and Figure 2 As shown, the flame-retardant composite material includes cross-linked flame-retardant particles with an average particle size of 21 nm and an average particle size of 53 nm for the flame-retardant composite material.

[0087] Example 2

[0088] Weigh 0.3g of ammonium polyphosphate and dissolve it in 5mL of methyl methacrylate monomer. Sonicate for 10min to disperse evenly and obtain the first solution.

[0089] Weigh 0.4g of sodium dodecylbenzenesulfonate and dissolve it in 80mL of deionized water. Stir mechanically for 10min to disperse it evenly and obtain a second solution.

[0090] The first solution was added dropwise to the second solution and stirred to disperse it evenly. Then, it was emulsified for 30 minutes to obtain the first mixture.

[0091] Argon gas was introduced into the first emulsified mixture and stirred for 30 minutes. Then, the mixture was heated to 85°C and 0.4 g of ammonium sulfate was added. The mixture was reacted for 6 hours to obtain the second mixture.

[0092] After the reaction is complete, heating of the second mixed solution is stopped, and sodium chloride is added to the second mixed solution at 85°C until the sodium chloride concentration in the second mixed solution reaches saturation. The solution is then centrifuged at 9600 rpm and dried to obtain the flame-retardant composite material. The flame-retardant composite material comprises cross-linked flame-retardant particles with an average particle size of 12 nm, and the average particle size of the flame-retardant composite material is 33 nm.

[0093] Example 3

[0094] Weigh 0.3g of ammonium polyphosphate and dissolve it in 4mL of methyl methacrylate monomer. Sonicate for 10min to disperse evenly and obtain the first solution.

[0095] Weigh 0.4g of sodium dodecylbenzenesulfonate and dissolve it in 80mL of deionized water. Stir mechanically for 10min to disperse it evenly and obtain a second solution.

[0096] The first solution was added dropwise to the second solution and stirred to disperse it evenly. Then, it was emulsified for 30 minutes to obtain the first mixture.

[0097] Argon gas was introduced into the first emulsified mixture and stirred for 30 minutes. Then, the mixture was heated to 80°C and 0.3 g of ammonium sulfate was added. The mixture was reacted for 4 hours to obtain the second mixture.

[0098] After the reaction is complete, heating of the second mixed solution is stopped, and sodium chloride is added to the second mixed solution at 80°C until the sodium chloride concentration in the second mixed solution reaches saturation. The solution is then centrifuged and dried at 8000 rpm to obtain the flame-retardant composite material. The flame-retardant composite material comprises cross-linked flame-retardant particles with an average particle size of 48 nm, and the average particle size of the flame-retardant composite material is 195 nm.

[0099] Example 4

[0100] The flame-retardant composite material was prepared according to the method of Example 1, except that the polymerization temperature was 70°C.

[0101] Example 5

[0102] The flame-retardant composite material was prepared according to the method of Example 1, except that the polymerization temperature was 90°C.

[0103] Example 6

[0104] The flame-retardant composite material was prepared according to the method of Example 1, except that the centrifugation speed was 7000 rpm.

[0105] Example 7

[0106] The flame-retardant composite material was prepared according to the method of Example 1, except that the centrifugation speed was 10,000 rpm.

[0107] Comparative Example 1

[0108] The flame-retardant composite material was prepared according to the method of Example 1, the only difference being that the flame-retardant composite material was obtained by direct cooling and separation after the polymerization reaction. The flame-retardant composite material comprises multiple flame-retardant particles, such as... Figure 3 As shown, the average particle size of the flame-retardant particles is 22 μm.

[0109] Comparative Example 2

[0110] The flame-retardant composite material was prepared according to the method of Example 1, except that the polymerization reaction time was 6 hours. The average particle size of the flame-retardant particles in the obtained flame-retardant composite material was 73 nm, and the average particle size of the flame-retardant composite material was 293 nm.

[0111] Comparative Example 3

[0112] The flame-retardant composite material was prepared according to the method of Example 1, except that the polymerization reaction time was 3 hours, the average particle size of the flame-retardant particles in the obtained flame-retardant composite material was 7 nm, and the average particle size of the flame-retardant composite material was 22 nm.

[0113] The flame-retardant composite materials prepared in the above embodiments and comparative examples were added to the electrolyte for testing. The testing methods included:

[0114] 10% of the flame-retardant composite material was added to an electrolyte of type KLD-LP11 (solute: 1.2 mol / L LiPF6; solvent: EC:EMC volume ratio: 3:7), and the self-extinguishing time and conductivity of the electrolyte of the battery were tested.

[0115] The test method for electrolyte self-extinguishing time includes: placing approximately 0.5g of electrolyte into a petri dish with a diameter of 7cm. The electrolyte is then exposed to the flame of a burner for 3s. If ignition occurs, the time from when the burner is removed (after 3s) until the flame is completely extinguished is recorded, and the ratio of burning time to mass is recorded as SET.

[0116] The electrolyte conductivity was tested using a Consort K912 conductivity meter with an SK21T microelectrode probe, conducted in an argon-filled glove box. The conductivity meter was calibrated outside the glove box using a KCl standard solution. At room temperature, 4 mL of electrolyte sample was placed in a 10 mL centrifuge tube. The electrode probe was then inserted into the electrolyte in the centrifuge tube, ensuring the electrolyte submerged at least one-third of the probe tip. The conductivity value was read after the reading stabilized. The test results are shown in Table 1.

[0117] Table 1

[0118]

[0119] The flame-retardant composite materials prepared in the above embodiments and comparative examples were added to the battery electrodes as conductive agents for testing. The testing methods included:

[0120] The conductive agent in the positive / negative electrode of the 1Ah NCM811|| graphite standard soft-pack battery was replaced with the aforementioned flame-retardant composite material, with the flame-retardant composite material accounting for 50% of the mass of the conductive agent. The battery was then tested for thermal abuse and cycle performance.

[0121] The thermal abuse test method includes the following steps: The thermal abuse test is conducted in an explosion-proof cabinet. First, a soft-pack battery is placed in a heating device with an adjustable nut, and two mica sheets separate the battery from the heating device. A ceramic heating element is placed between one of the mica sheets and the battery. The ceramic element is initially heated rapidly to 200°C and then heating is stopped. A K-type thermocouple is fixed between the other side of the battery and another mica sheet, and the temperature change during the thermal abuse process is recorded.

[0122] The cycle performance test method included: preparing a 1Ah NCM811||graphite standard pouch cell by adding microcapsules with 5% electrolyte mass fraction, and charging it to 4.2V and discharging it to 2.75V at a constant current of 0.5C using a Blue Electric Charge-Discharge Machine (CT3002A) at 25℃, repeating the test for 400 cycles. The test results are shown in Table 2.

[0123] Table 2

[0124]

[0125] As can be seen from the table above:

[0126] (1) Compared with Examples 4-5, Example 1 of this application controls the temperature of the polymerization reaction to ensure the polymerization rate, so that the polymer monomers can be coated on the surface of the flame retardant material. If the temperature of the polymerization reaction is relatively high, the polymer monomers may not be able to completely coat the flame retardant material; if the temperature of the polymerization reaction is relatively low, the polymerization reaction rate may be slow, which not only affects the production efficiency, but also results in large particle size and few interstitial structures in the flame retardant composite material, thus affecting the electrochemical performance of the battery.

[0127] (2) Compared with Examples 6-7, Example 1 of this application shows that the centrifugation speed is controlled in this application to obtain microcapsules of more suitable size, which is more conducive to forming a 3D Internet structure. If the speed is relatively low, the microcapsule size may be large, the material is very easy to agglomerate, and the advantages of the 3D Internet structure cannot be truly brought into play. If the speed is relatively fast, the microcapsule size may be small, the individual capsules are more dispersed, and the 3D interconnected structure cannot be realized.

[0128] (3) Compared with Comparative Examples 1-3, Example 1 of this application shows that the average particle size of the flame-retardant composite material is controlled by this application, which has the advantages of excellent dispersibility and conductivity. If the average particle size is relatively large, the flame-retardant composite material may have poor dispersibility, which will not only affect the conductivity of the battery, but also easily lead to uneven dispersion of the flame retardant released by the flame-retardant particles during thermal runaway, and will not be able to block the thermal runaway reaction in time. Furthermore, the average particle size of the flame-retardant particles is controlled by this application, which can effectively ensure that a stable cross-linked structure can be formed between the flame-retardant particles and that there is a stable gap between the flame-retardant particles, thereby improving the conductivity of the flame-retardant composite material. If the average particle size of the flame-retardant particles is relatively large, the gap structure formed may be too large, which is not conducive to the ion transport performance of the gap structure. If the average particle size of the flame-retardant particles is relatively small, the amount of flame retardant coated will be small, which will affect the flame-retardant effect.

[0129] In summary, the flame-retardant composite material of this application uses a conductive organic layer as the outer shell of the flame-retardant composite material, thereby reducing the impact of flame retardant addition on battery conductivity. Furthermore, through cross-linking of the outer surface of the conductive organic layer, the flame-retardant composite material has an interstitial structure, increasing ion transport channels and ensuring the electrochemical performance of the battery. In addition, when the battery experiences thermal runaway, the cross-linking sites preferentially break, and each flame-retardant particle breaks and separates, improving the dispersibility of the flame-retardant particles. The flame-retardant particles are dispersed to various parts of the battery, and then the conductive organic layer on the surface of the flame-retardant particles breaks, releasing the flame retardant, effectively improving battery safety.

[0130] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0131] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A flame-retardant composite material, characterized in that, The flame-retardant composite material includes at least two cross-linked flame-retardant particles. Each flame-retardant particle includes a flame retardant and a conductive organic layer coated on the surface of the flame retardant. The conductive organic layers on the surfaces of two adjacent flame-retardant particles are cross-linked to form an agglomerated flame-retardant composite material with a gap structure. Multiple agglomerated flame-retardant composite materials are cross-linked to form a 3D internet structure. The average particle size of the flame-retardant particles is 10 nm to 50 nm.

2. The flame-retardant composite material as described in claim 1, characterized in that, The average particle size of the flame-retardant composite material is 30nm~200nm.

3. The flame-retardant composite material as described in claim 1, characterized in that, The flame-retardant composite material also satisfies at least one of the following conditions: (1) The flame retardant includes at least one of phosphorus-based flame retardants, nitrogen-based flame retardants, halogen-based flame retardants and metal compound flame retardants; (2) The material of the conductive organic layer includes at least one of ion-conducting organic materials and electronically conductive organic materials.

4. The flame-retardant composite material as described in claim 3, characterized in that, The conductive organic layer is made of at least one of polymethyl methacrylate and polyacrylonitrile.

5. The flame-retardant composite material according to any one of claims 1-4, characterized in that, The average thickness of the conductive organic layer is 20 nm to 50 nm.

6. A method for preparing a flame-retardant composite material according to any one of claims 1-5, characterized in that, The preparation method includes: Prepare a first mixture containing a flame retardant and a conductive polymeric monomer; An initiator is added to the first mixture to cause the conductive polymer monomer to undergo a polymerization reaction on the surface of the flame retardant, thereby obtaining a second mixture; At the polymerization reaction temperature, a dissolved salt is added to the second mixture, the concentration of the dissolved salt in the second mixture being saturated. The second mixture is then centrifuged and dried to prepare the flame-retardant composite material.

7. The preparation method according to claim 6, characterized in that, The polymerization reaction is carried out at a temperature of 75℃~85℃.

8. The preparation method according to claim 6, characterized in that, The dissolved salt includes at least one of sodium chloride, potassium chloride, and magnesium chloride.

9. The preparation method according to claim 6, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The first mixture also includes an emulsifier; (2) The initiator includes ammonium persulfate; (3) The mass ratio of the flame retardant to the conductive polymer monomer is (1~3):1; (4) The mass ratio of the initiator to the conductive polymer monomer is 1: (80~120).

10. The preparation method according to claim 9, characterized in that, The emulsifier includes at least one of sodium dodecylbenzenesulfonate, nonylphenol ethylene oxide ether, and sodium dodecyl sulfate.

11. The preparation method according to any one of claims 6-10, characterized in that, The centrifuge speed is 8000 rpm to 9800 rpm.

12. A battery, characterized in that, The battery comprises the flame-retardant composite material according to any one of claims 1-5 or the flame-retardant composite material prepared by the preparation method of the flame-retardant composite material according to any one of claims 6-11.